Temporal stability and community assembly mechanisms in healthy broiler cecum - Ameer, Aqsa; Cheng, Youqi; Saleem, Farrukh; Uzma,; McKenna, Aaron; Richmond, Anne; Gundogdu, Ozan; Sloan, William T.; Javed, Sundus; Ijaz, Umer Zeeshan (Frontiers in Microbiology, 2023)
In recent years, there has been an unprecedented advancement in in situ analytical approaches that contribute to mechanistic understanding of microbial communities by explicitly incorporating ecology and studying their assembly. In this study, we have analyzed the temporal profiles of healthy broiler cecal microbiome from day 3 to day 35 to recover the stable and varying components of microbial communities. During this period, the broilers are fed three different diets chronologically, and therefore, we have recovered signature microbial species that dominate during each dietary regime. Since broilers were raised in multiple pens, we have also parameterized these as an environmental condition to explore microbial niches and their overlap. All of these analyses were performed in view of different parameters such as body weight (BW-Mean), feed intake (FI), feed conversion ratio (FCR) and age (Days), to link them to a subset of microbes that these parameters have a bearing upon. We found that gut microbial communities exhibited strong and statistically significant specificity to several environmental variables. Through regression models, genera that positively/negatively correlate with bird age were identified. Some short chain fatty acids (SCFAs) producing bacteria including Izemoplasmatales, Gastranaerophilales, and Roseburia are found in positive correlation with age. Certain pathogens such as Escherichia-Shigella, Sporomusa, Campylobacter, and Enterococcus negatively correlated with bird age, which indicated a high disease risk in initial days. Moreover, majority of pathways involved in amino acid biosynthesis were also positively correlated with bird’s age. Some probiotic genera associated with improved performance, included Oscillospirales;UCG−010, Shuttleworthia, Bifidobacterium and Butyricicoccaceae;UCG−009. In general, predicted Antimicrobial Resistance Genes (piARGs) contributed at a stable level, but there is slight increase in abundance when the diet was changed. To the best of our knowledge, this is one of the first studies that is looking at the stability, complexity, and ecology of natural broiler microbiota development in a temporal setting.